2000
DOI: 10.1164/ajrccm.161.4.9907143
|View full text |Cite
|
Sign up to set email alerts
|

Relation of FEV1to Clinical Outcomes during Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: FEV(1) is an objective measure of airflow obstruction used in clinical practice and in therapeutic trials. The precise relationship of FEV(1) to clinical outcomes is generally uncertain. As part of a randomized trial to assess systemic corticosteroid efficacy, we obtained serial FEV(1) measurements in patients hospitalized for exacerbations of chronic obstructive pulmonary disease (COPD). Over the first 14 Study Days at least one FEV(1) value was obtained in 261 subjects. Sixty-four of these subjects experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 23 publications
2
44
0
6
Order By: Relevance
“…Niewoehner et al found that relatively small differences in FEV 1 have a substantial impact on clinical outcome. 20 Among the subjects who received nebulized furosemide, those with lower baseline FEV 1 had better dyspnea improvement (see the Figure). Since patients with lower FEV 1 are less able to bronchodilate, this improvement might also be attributed to an effect of nebulized furosemide on dyspnea relief that is independent of bronchodilation.…”
Section: Discussionmentioning
confidence: 94%
“…Niewoehner et al found that relatively small differences in FEV 1 have a substantial impact on clinical outcome. 20 Among the subjects who received nebulized furosemide, those with lower baseline FEV 1 had better dyspnea improvement (see the Figure). Since patients with lower FEV 1 are less able to bronchodilate, this improvement might also be attributed to an effect of nebulized furosemide on dyspnea relief that is independent of bronchodilation.…”
Section: Discussionmentioning
confidence: 94%
“…FEV1 measurements are a highly predictive factor in the clinical outcome of COPD exacerbations [20]. In contrast to other trials patients who had already received systemic steroids prior to hospital admission were not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by NIEWOEHNER et al [37] of acute exacerbations of COPD, FEV1 change was associated with clinical response to treatment. An FEV1 improvement of ,100 mL was associated with a higher relapse rate.…”
Section: Anchor-based Midmentioning
confidence: 95%
“…However, even small changes in postbronchodilator FEV1 following acute treatment were found to be associated with meaningful clinical outcomes [36][37][38].…”
Section: Lung Functionmentioning
confidence: 99%
See 1 more Smart Citation